Environmental Politics Casebook: Genetically Modified Foods - Miller, Norman (CRC Press, 2009)
Environmental Politics Casebook: Genetically Modified Foods includes testimony, journal and newspaper articles, book chapters, and interest group communications such as press releases and on-line briefs, as well as other studies and reports that constitute the principal elements of the public debate on the genetic modification of food. A companion to Environmental Politics: Interest Groups, the Media, and the Making of Policy, it provides the substantive, detailed, case-in-point application for practices and principles previously discussed only in theory, keeping the basic text compact and current.